Asia Pacific in World Politics - McDougall, Derek, 1945- (New Delhi Viva Books, 2008)
"In this thorough, analytical introduction to Asia Pacific's dynamic role in contemporary world politics, Derek McDougall focuses on the region's major state actors - China, Japan, and the United States - as well as on the conflicts involving Taiwan and Korea, developments in Southeast Asia, and the influences of Russia, Australia, and a range of international organizations."--Jacket.
Include Acronyms and Abbreviation, Bibliography, Index and Maps.
Keywords: Asia -- Pacific Area -- Diplomatic Relations